2008
DOI: 10.1158/0008-5472.can-07-3224
|View full text |Cite
|
Sign up to set email alerts
|

A First-Generation Multiplex Biomarker Analysis of Urine for the Early Detection of Prostate Cancer

Abstract: Although prostate-specific antigen (PSA) serum level is currently the standard of care for prostate cancer screening in the United States, it lacks ideal specificity and additional biomarkers are needed to supplement or potentially replace serum PSA testing. Emerging evidence suggests that monitoring the noncoding RNA transcript PCA3 in urine may be useful in detecting prostate cancer in patients with elevated PSA levels. Here, we show that a multiplex panel of urine transcripts outperforms PCA3 transcript alo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
285
0
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 367 publications
(305 citation statements)
references
References 32 publications
8
285
0
12
Order By: Relevance
“…Several studies to date have demonstrated the detection of the TMPRSS2:ERG fusion transcripts in urine. 44,45,67 These studies, and other unpublished reports, demonstrate a high specificity. Unlike PSA, which can be elevated in benign conditions as well as cancer, the presence of TMPRSS2:ERG transcripts has only been reported in neoplastic cells.…”
Section: Diagnostic and Clinical Therapy Implicationssupporting
confidence: 76%
“…Several studies to date have demonstrated the detection of the TMPRSS2:ERG fusion transcripts in urine. 44,45,67 These studies, and other unpublished reports, demonstrate a high specificity. Unlike PSA, which can be elevated in benign conditions as well as cancer, the presence of TMPRSS2:ERG transcripts has only been reported in neoplastic cells.…”
Section: Diagnostic and Clinical Therapy Implicationssupporting
confidence: 76%
“…11 On the other hand, AMACR transcripts normalized to PSA were not statistically significant predictors of CaP in a recent multiplex study of urine markers (see below). 12 GSTP1 (glutathione S-transferase P1) belongs to a family of enzymes involved in protecting DNA from free radicals. CaP is associated with the loss of GSTP1 expression due to promoter hypermethylation.…”
Section: Advantages and Limitations Of Novel Urine Markersmentioning
confidence: 99%
“…Current biopsy strategies may miss heterogenous tumor foci, and urine-based assay would have a great advantage because the cells from multiple cancerous foci of whole prostate could be released and collected. 69 Laxman et al 12 reported that a multiplex panel of urine transcripts outperforms PCA3 transcript and serum PSA alone in detecting CaP. Expression of seven putative prostate cancer biomarkers was measured (PCA3, PSA, GOLPH2, SPINK1, AMACR, TMPRSS2/ERG, TFF3) by qRT-PCR in urine samples.…”
Section: Multiplex Analysis Of Urine Markers and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations